(-4)(p+8)=12

Simple and best practice solution for (-4)(p+8)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-4)(p+8)=12 equation:


Simplifying
(-4)(p + 8) = 12

Reorder the terms:
-4(8 + p) = 12
(8 * -4 + p * -4) = 12
(-32 + -4p) = 12

Solving
-32 + -4p = 12

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '32' to each side of the equation.
-32 + 32 + -4p = 12 + 32

Combine like terms: -32 + 32 = 0
0 + -4p = 12 + 32
-4p = 12 + 32

Combine like terms: 12 + 32 = 44
-4p = 44

Divide each side by '-4'.
p = -11

Simplifying
p = -11

See similar equations:

| 150m-100m+39000=40000-150m | | 22+2z=37+6*z | | 12w-19w-1=13 | | w(w-13)=0 | | -x+2(4-x)=-4 | | Sin(x)=-1 | | 6y=-120 | | 6x=32 | | 16=p-(-3) | | 10m+8b-12=0 | | -15+7x=-79 | | (x+3)+(y-5)=36 | | -25(d+2)= | | 14x+9y=310 | | 16.4(2x+11)=6x+33 | | 2990=4*660+6y | | 12x+9y=310 | | -2(z-9)=-24 | | y-10=-2(x+2) | | 7u-6u+2=20 | | 2990=4*650+6y | | .5x-9=.2x | | Y-2=-1(x+7) | | 4(cos^2(2x))-2=0 | | -25d-50= | | 2990=4*640+6y | | x+y-8x+6y-125=0 | | X-15=-50 | | 70=(4y-30) | | 3x-10y=-22 | | (1-x)+3x=-2(x+1) | | 5x-20+2x+53=180 |

Equations solver categories